Potencial antifúngico e modulador do óleo essencial do quimiotipo III (limonemo e carvona) de Lippia alba (Mill.) N. E. Brown - Sales, Gleilton Weyne Passos (2022)
Fungal diseases and resistance to antifungal drugs are a threat to the modern world, and phytotherapy is an alternative used in folk medicine to combat infections. Among the species stands out Lippia alba (lemon balm), which is used in traditional medicine to treat indigestion, respiratory diseases, anxiety, pain, inflammation, fever and hypertension. The aim of this study was to evaluate the antifungal activity of the essential oil from the leaves of Lippia alba (Mill.) N. E. Brown. chemotype III (limonemo and carvone) (OELaIII). Brown. (OELaIII), its modulatory effect on antifungals of clinical use, as well as the mechanism of action on Candida reference strains (C. albicans ATCC 64124, C. albicans ATCC 90028, C. albicans ATCC 90029, C. albicans ATCC 44858, C. albicans ATCC 10231, C. tropicalis ATCC 750, C. tropicalis ATCC 13803 and C. parapsilosis ATCC 90018). For the evaluation of the antifungal activity, the Inhibitory Concentration (MIC) and the Minimum Lethal Concentration (MLC) of OELaIII, the effect of the exposure time to OELaIII on microbial viability, the modulating effect of OELaIII on the activity of clinical use antifungals were determined. For the mechanism of action of OELaIII, the release of genetic material, the release of proteins and the mechanisms of action of sorbitol and ergosterol were determined. The action of OELaIII concentrations on the virulence factors activity (biofilm, proteinase and lipase) and its hemolytic activity were also evaluated. The result of the analysis of OELaIII indicated the presence of 11 constituents, with predominance of carvone (58.15%) and limonene (25.37%). OELaIII was able to inhibit the growth of all microorganisms tested, with MIC and CLM ranging from 0.078 to 1.25 mg/mL, and CIMB and CMEB ranging from 0.156 to 5 mg/mL. The exposure time assay demonstrated that OELaIII was able to eliminate all strains within two hours of exposure. OELaIII showed different modulation profiles in association with clinically used antifungal drugs, the best association being observed for the combination with ketoconazole. OELaIII was able to promote the loss of cytoplasmic material (nucleic acids and proteins), with lysis of the cell envelope and moderate hemolytic activity. The results of the study indicate that OELaIII has an excellent antifungal potential, with fungicidal and fungistatic mechanism based on the disruption of the microbial envelope, besides presenting an excellent modulating effect when associated with the antifungal ketoconazole.